1994
DOI: 10.1677/joe.0.1420581
|View full text |Cite
|
Sign up to set email alerts
|

Physiological roles of thyrotrophin-releasing hormone and vasoactive intestinal peptide on the pulsatile secretory patterns of prolactin in pituitary-grafted female rats

Abstract: Much is known about the fact that thyrotrophin-releasing hormone (TRH) and vasoactive intestinal peptide (VIP) stimulate prolactin secretion but areas of uncertainty remain. This work was undertaken to describe the effects of TRH and VIP on the pulsatile secretion pattern of prolactin, in adult sham-operated and pituitary-grafted hyperprolactinaemic female rats. Two pulses of TRH (1 microgram/rat) or one pulse of VIP (20 micrograms/rat) were given 60 or 120 min after the period of blood sampling. Pituitary gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…The sharp rise of prolactin concentrations measured in coincidence with the TSH rise 20 min after intravenous TRH injection shows the likewise stimulation of thyrotrophic and lactotrophic pituitary cells and confirms that TRH is a potent PRF in the dog [33] as described in other species (sheep [14]; rat [17]). Suppression of this TRH-mediated stimulation of prolactin release by cabergoline suggests dopaminergic suppression of the sensitivity of the lactotrophs towards TRH.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The sharp rise of prolactin concentrations measured in coincidence with the TSH rise 20 min after intravenous TRH injection shows the likewise stimulation of thyrotrophic and lactotrophic pituitary cells and confirms that TRH is a potent PRF in the dog [33] as described in other species (sheep [14]; rat [17]). Suppression of this TRH-mediated stimulation of prolactin release by cabergoline suggests dopaminergic suppression of the sensitivity of the lactotrophs towards TRH.…”
Section: Discussionsupporting
confidence: 68%
“…Only a few years ago, a specific prolactin-release promoting peptide has been identified and characterised in the hypothalamus [11,12]. In addition, several other prolactin-stimulating factors have been reported, such as serotonin [13] and thyrotrophin-releasing hormone (TRH) [14][15][16][17][18]. In a recent study the strong prolactin stimulating effect of TRH was also demonstrated in cattle in vitro and in vivo when compared with the prolactin release induced by a bovine posterior pituitary extract and prolactin releasing peptide [19].…”
Section: Introductionmentioning
confidence: 99%
“…PRL secretion exhibits low-amplitude pulsatility (40,42), and therefore measurements integrated over time better reflect basal PRL secretion than do singular determinations. Blood was sampled six times at 10-min intervals over a 50-min period, based on data by Lopez et al (42) and Lafuente et al (40) that a PRL pulse lasts 16 -25 min and would be expected to occur every 40 min.…”
Section: Methodsmentioning
confidence: 99%
“…PRL challenge tests by intravenous TRH bolus injection were completed one time during the baseline period and one time per week during the experimental period in the experimental subgroup. Blood was sampled immediately before and at 10, 20, and 40 min after intravenous administration of TRH (10 g/kg), based on previous studies (40,48). The total volume of blood drawn was 2.1 ml, with volume and RBC replacement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation